Neue Perspektiven der Unternehmensgeschichte [New Perspectives in Business History]: Edited by Nina Kleinöder, Christian Marx, Boris Gehlen, Juliane Czierpka, Brill/Schöningh, Paderborn, 2024 - Staffel, Florian (Business History)

Datenraum Kultur - Neue Forschung aus dem Projekt - Althaus, Maike

Startschuss für die digitale Zukunft - Das Digital Talents Program geht in die nächste Runde - Kundisch, Dennis

Zahlenmuster und Brüche: Eine Lernumgebung zum algebraischen Denken - Rezat, Sebastian; Doligkeit, Nadja (mathematik lehren)

In vacuum metasurface for optical microtrap array - Li, Donghao; Liao, Qiming; Xu, Beining; Zentgraf, Thomas; Narvaez Castaneda, Emmanuel; Zhou, Yaoting; Qin, Keyu; Xu, Zhongxiao; Shen, Heng; Huang, Lingling (Optics Express)
Optical tweezer arrays of laser-cooled and individually controlled particles have revolutionized atomic, molecular, and optical physics. They afford exquisite capabilities for applications in quantum simulation of many-body physics, quantum computation, and sensing. Underlying this development is the technical maturity of generating scalable optical beams, enabled by active components and a high numerical aperture objective. However, such a complex combination of bulk optics outside the vacuum chamber is very sensitive to any vibration and drift. Here, we demonstrate the generation of a 3 × 3 static tweezer array with a single chip-scale multifunctional metasurface element in vacuum, replacing the meter-long free space optics. Fluorescence counts on the camera validate the successful trapping of the atomic ensemble array and showcase a promising strategy for integrated photonics with cold atom systems. The introduction of a polarization independent dual-wavelength metasurface significantly enhances fluorescence collection efficiency while reducing experimental complexity. This approach paves the way for scalable neutral atom platforms and offers a compelling route towards the realization of next generation quantum metasurfaces.

Christoph Haar (Hg.): Slavery, Law and Religion in the Early Modern Period (Law and Religion in the Early Modern Period/ Recht und Religion in der Frühen Neuzeit. 7). Leiden, Boston 2024 - Priesching, Nicole (Theologische Revue)

Berichtete Praktiken der Lernbegleitung bei der Förderung von arithmetischen Basiskompetenzen - Neufeld, Inga (Was ist wichtig? Perspektiven auf den Mathematikunterricht der Grundschule)

Antonio Negri, Spinoza, Marx, and Digital Capitalism. - Fuchs, Christian (Philosophy and Social Criticism)

Technikrecht - Ensthaler, Jürgen; Gesmann-Nuissl, Dagmar; Müller, Stefan

A Measurement Setup for the Determination of Temperature-Dependent Viscoelastic Material Parameters Using an Ultrasonic Pulse-Echo Technique - Dreiling, Dmitrij; Itner, Dominik; Gravenkamp, Hauke; Birk, Carolin; Henning, Bernd (2025 International Congress on Ultrasonics)

Explanation needs and ethical demands: unpacking the instrumental value of XAI - Alpsancar, Suzana; Buhl, Heike M.; Matzner, Tobias; Scharlau, Ingrid (AI and Ethics)

Explainability and AI Governance - Reijers, Wessel; Matzner, Tobias; Alpsancar, Suzana (Digital Development. Technology, Ethics and Governance)

Monitoring the curing process of adhesive bonds using selective excitation of guided ultrasonic waves - Zeipert, Henning; Nellius, Tom; Schönlau, Nikolas; Wippermann, Mareen; Claes, Leander; Nicolai, Marcel; Prager, Jens; Henning, Bernd (2025 International Congress on Ultrasonics)

The structure of the double discriminant - Anderson, Theresa C.; Asarhasa, Ufuoma V.; Bertelli, Adam; Gundlach, Fabian; O'Dorney, Evan M. (arXiv:2507.16138)
For a polynomial $f(x) = \sum_{i=0}^n a_i x^i$, we study the double discriminant $DD_{n,k} = \operatorname{disc}_{a_k} \operatorname{disc}_x f(x)$. This object has been well studied in algebraic geometry, but has been brought to recent prominence in number theory by its key role in the proof of the Bhargava--van der Waerden theorem. We bridge the knowledge gap for this object by proving an explicit factorization: $DD_{n,k}$ is the product of a square, a cube, and possibly a linear monomial. Our proof is entirely algebraic. We also investigate other aspects of this factorization.

"Himmel" und "Hölle" als Sinnbilder der Seele - Garske, Volker

Forward-Biased Silicon Phase Shifter Modeling for Electronic-Photonic Co-Simulation and Validation in a 250 nm EPIC BiCMOS Technology - Schwabe, Tobias; Kress, Christian; Kruse, Stephan; Weizel, Maxim; Rhee, Hanjo; Scheytt, J. Christoph (Journal of Lightwave Technology)
Keywords: Integrated circuit modeling; Capacitance; Silicon; Modulation; Adaptation models; Semiconductor device modeling; Bandwidth; Data communication; electrooptical transmitter; equalization; free-carrier-plasma dispersion effect; modelling; optical modulator; phase shifter; silicon photonics

A Photonic Assisted Visible Light FMCW Lidar System for Large Aperture Phased Array MIMO Based on LEDs - Kruse, Stephan; Brockmeier, Jan; Schwengelbeck, Max; Schwabe, Tobias; Scheytt, J. Christoph (2025 55th European Microwave Conference (EuMC))
Keywords: Phased arrays; Optical fibers; Optical fiber sensors; Laser radar; Optical variables measurement; Apertures; Light emitting diodes; Optical receivers; Optical transmitters; Optical modulation; Lidar; light detection and ranging; FMCW; frequency modulated contentious wave; visible light sensing (VLS); visible light communication (VLC); automotive headlights; light emitting diode (LED); microwave photonics; wireless sensing

Analysis and Design of Forward Biased Silicon Photonics Phase Shifter Equalizer Circuits - Schwabe, Tobias; Kress, Christian; Sadiye, Babak; Kruse, Stephan; Scheytt, J. Christoph (IEEE Access)
Keywords: Optical attenuators; Equalizers; Phase shifters; Optical modulation; Electro-optic modulators; Optical amplifiers; Circuits; Silicon photonics; Optical saturation; Integrated circuit modeling; Data communication; equalization; electro-optical transmitter; silicon photonics; phase shifter; optical modulator; free-carrier plasma dispersion effect; driver architectures; biasing schemes

Electrooptical Integration of an Electronic Photonic Integrated Circuit Into Plastic Substrates Using Mid-Technology - Kruse, Stephan; Diri, Jabil; Mager, Thomas; Kress, Christian; Scheytt, J. Christoph (2025 55th European Microwave Conference (EuMC))
Keywords: Optical fibers; Integrated optics; Semiconductor device measurement; Laser radar; Optical device fabrication; Photonic integrated circuits; Microwave theory and techniques; Optical fiber devices; Plastics; Substrates; Microwave photonics; photonic radar; optical LO distribution; mechatronic integrated device (MID)

Antennenvorrichtung zum Aussenden von elektromagnetischer Strahlung für ein Kraftfahrzeug sowie Kraftfahrzeug - Kruse, Stephan; Meinecke, Marc-Michael; Gisder, Thomas; Simoni, Renato; González-Huici, Maria Antonia; Greiff, Christian; Mateos-Nunez, David; Danklmayer, Andreas; Ladan, Julien; Kurz, Heiko Gustav